2015
DOI: 10.3346/jkms.2015.30.5.598
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognostic Impact of Bacterial Infection in Hospitalized Patients with Alcoholic Liver Disease

Abstract: Bacterial infection is an important cause of death in patients with liver cirrhosis. The aim of this study was to investigate the clinical characteristics and prognostic impact of bacterial infection in hospitalized patients with alcoholic liver disease (ALD). We retrospectively analyzed data from 409 patients consecutively admitted to a tertiary referral center with ALD diagnosis. Of a total of 544 admissions, 133 (24.4%) cases presented with bacterial infection, of which 116 were community-acquired whereas 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Liver cirrhosis complicated with sepsis has the poorest prognosis. For example, patients with SBP that stems from pulmonary infection can progress to multiple infections and sepsis, bearing an increased mortality . Our study showed that multi‐site infections in patients with liver cirrhosis and SIRS were independent risk factors for death (HR = 19.427; CI, 7.484–50.431; P < 0.001).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Liver cirrhosis complicated with sepsis has the poorest prognosis. For example, patients with SBP that stems from pulmonary infection can progress to multiple infections and sepsis, bearing an increased mortality . Our study showed that multi‐site infections in patients with liver cirrhosis and SIRS were independent risk factors for death (HR = 19.427; CI, 7.484–50.431; P < 0.001).…”
Section: Discussionmentioning
confidence: 62%
“…For example, patients with SBP that stems from pulmonary infection can progress to multiple infections and sepsis, bearing an increased mortality. 3,34 Our study showed that multi-site infections in patients with liver cirrhosis and SIRS were independent risk factors for death (HR = 19.427; CI, 7.484-50.431; P < 0.001). We found that some cirrhotic patients with bacterial infection did not have SIRS and some patients with SIRS had nonbacterial infection.…”
Section: Discussionmentioning
confidence: 75%
“…Ten articles were excluded (two articles had no outcome of interest, while eight articles did not relate to a study in the subjects of interest). Data was extracted from six cohort studies (five retrospective cohort studies (5,13,14,19,20) and one prospective cohort study (4)) involving 1,264 patients (507 had SIRS), and four cohort studies (all retrospective cohort studies (3,14,21,22)) involving 57,529 patients (1,449 had sepsis). There were two studies assessing the mortality comparing AH patients with SIRS versus sepsis involving 527 patients (all retrospective cohort studies (5,13)).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies addressing the importance of SIRS in patients with AH have been conducted (5,13,14). Thus, to better characterize the effect of SIRS, we conducted a systematic review and meta-analysis of the observational studies in the literature that compared the risk of mortality in hospitalized patients with AH who had SIRS vs. non-SIRS as our primary outcome and sepsis vs. non-sepsis as our secondary outcome.…”
mentioning
confidence: 99%
“…Colonial and cellular morphology of the culture plates were observed, and necessary biochemical tests were carried out. 11 Antibiotics susceptibility test and ESBL screening This was done according to Clinical Laboratory Standard Institute (CLSI) Guidelines. 12 Standard antimicrobial discs for Gram negative and Gram positive organisms was placed onto the surface of the inoculated agar plates accordingly and incubated for 24 hours.…”
Section: Assay Procedures For Concomitant Bacteriamentioning
confidence: 99%